Konsep Pendidikan Adab dalam Kitab Al-Jāmi‘ Bulūgh al-Marām Karya Al-Imam Ibnu Hajar Al-Asqalani dan Relevansinya dengan Tujuan Pendidikan Nasional - Muhammad Syahdan; Iskandar Yusuf (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
Education of adab constitutes a fundamental foundation in shaping individuals with noble character. In the context of Islamic education, the concept of adab holds a central position and serves as a primary objective of the educational process. This article aims to examine the concept of adab education as presented in Al-Jāmi‘ Bulūgh al-Marām by Al-Imam Ibnu Hajar Al-Asqalani and to analyze its relevance to the objectives of National Education. This study employs a qualitative method with a library research approach. The primary data source is the book Bulūgh al-Marām, while secondary sources include books, scholarly journals, and official documents related to national education. The findings indicate that the concept of adab education in Bulūgh al-Marām emphasizes spiritual, moral, and social development, which aligns with the objectives of National Education, particularly in forming individuals who are faithful, pious, morally upright, and responsible. Therefore, adab education from the perspective of hadith remains highly relevant and can serve as a conceptual foundation for strengthening character education in Indonesia.   Keywords: adab education; Bulūgh al-Marām; Ibnu Hajar Al-Asqalani; Islamic education; national education objectives.   AbstrakPendidikan adab merupakan fondasi utama dalam pembentukan karakter manusia yang berakhlak mulia. Dalam konteks pendidikan Islam, konsep adab memiliki kedudukan yang sangat penting dan menjadi tujuan utama dari proses pendidikan. Artikel ini bertujuan untuk mengkaji konsep pendidikan adab dalam kitab Al-Jāmi‘ Bulūgh al-Marām karya Al-Imam Ibnu Hajar Al-Asqalani serta menganalisis relevansinya dengan tujuan Pendidikan Nasional. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan (library research). Sumber data utama adalah kitab Bulūgh al-Marām, sedangkan sumber pendukung berasal dari buku, jurnal ilmiah, dan dokumen resmi terkait pendidikan nasional. Hasil penelitian menunjukkan bahwa konsep pendidikan adab dalam Bulūgh al-Marām mencakup pembinaan sikap spiritual, moral, dan sosial yang selaras dengan tujuan Pendidikan Nasional, khususnya dalam pembentukan manusia yang beriman, bertakwa, berakhlak mulia, dan bertanggung jawab. Dengan demikian, pendidikan adab dalam perspektif hadis memiliki relevansi yang kuat dan dapat dijadikan landasan dalam penguatan pendidikan karakter di Indonesia.   Kata kunci: pendidikan adab; Bulūgh al-Marām; Ibnu Hajar Al-Asqalani; pendidikan Islam; tujuan Pendidikan Nasional.